ANTICANCER ACTIVITY TEST OF ETHANOL OF BENALU MANGGA LEAVES (DENDROPTHOE PENTANDRA) OBTAINED FROM SOME LOCATIONS IN INDONESIA AGAINST T47D BREAST CANCER CELL LINE - Putri, Astri Erdiani; Muti'ah, Roihatul; Bhagawan, Weka Sidha; Susanti, Erna (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.637, 2017)
Indonesia has so many kind of benalu (mistletoe), one of them wich has potential anticancer activity is benalu mangga ( Dendrophthoe petandra ). This research aims to determine the profile of anticancer activity of benalu mangga leaves extract from several locations in Indonesia against T47D cell line using invitro technique. The profile of anticancer activity can be used as one of the Requirement developed to be fitofarmaka. The separation of the active compound from leaves mistletoe mango do with ultrasonic maseration extraction method using a solvent of ethanol 96%. Each extract derived from 5 locations i.e. Kediri East Java, Pekalongan Central Java, Denpasar Bali, Lampung Sumatra and Bulungan Kalimantan at test level of toxicity against the cell line T47D breast cancer by MTT method Assay . Test statistic one way analysis of variance (Anova) with software SPSS version 16.0 used assess whether there is a difference significantly anticancer activity (IC 50 ) leaf extract mistletoe mango from five locations. The results showed that the IC 50 value of ethanol extracts of leaves mistletoe mango from the Kediri, Pekalongan, Denpasar, Lampung and Bulungan are 304.79 μg/ml, 4646.34 μg/ml, 417.01 μg/ml, 540.91 μg/ml, and 287.39 μg/ml. The results of the Anova statistical analysis shows that there are significant differences between the location of Kediri-Pekalongan, Bulungan-Pekalongan, Pekalongan and Denpasar-Lampung-Sumatra. The extracts of leaf mistletoe mango ( D . pentandra ) from Bulungan, Kediri and Denpasar location are potential to be anticancer agent.